Nonpainful remote electrical stimulation alleviates episodic migraine pain. (28th March 2017) - Yarnitsky, David; Volokh, Lana; Ironi, Alon; Weller, Boaz; Shor, Merav; Shifrin, Alla; Granovsky, Yelena
Abstract : Objective: To evaluate the efficacy of remote nonpainful electrical upper arm skin stimulation in reducing migraine attack pain. Methods: This is a prospective, double-blinded, randomized, crossover, sham-controlled trial. Migraineurs applied skin electrodes to the upper arm soon after attack onset for 20 minutes, at various pulse widths, and refrained from medications for 2 hours. Patients were asked to use the device for up to 20 attacks. Results: In 71 patients (299 treatments) with evaluable data, 50% pain reduction was obtained for 64% of participants based on best of 200-μs, 150-μs, and 100-μs pulse width stimuli per individual vs 26% for sham stimuli. Greater pain reduction was found for active stimulation vs placebo; for those starting at severe or moderate pain, reduction (1) to mild or no pain occurred in 58% (25/43) of participants (66/134 treatments) for the 200-μs stimulation protocol and 24% (4/17; 8/29 treatments) for placebo ( p = 0.02), and (2) to no pain occurred in 30% (13/43) of participants (37/134 treatments) and 6% (1/17; 5/29 treatments), respectively ( p = 0.004). Earlier application of the treatment, within 20 minutes of attack onset, yielded better results: 46.7% pain reduction as opposed to 24.9% reduction when started later ( p = 0.02). Conclusion: Nonpainful remote skin stimulation can significantly reduce migraine pain, especially when applied early in an attack. This is presumably by activating descending inhibition pathways via the conditioned pain modulation effect. This treatment may be proposed as an attractive nonpharmacologic, easy to use, adverse event free, and inexpensive tool to reduce migraine pain. ClinicalTrials.gov identifier: NCT02453399. Classification of evidence: This study provides Class III evidence that for patients with an acute migraine headache, remote nonpainful electrical stimulation on the upper arm skin reduces migraine pain.